Pengembangan Perangkat Pembelajaran Melalui In House Training Model Jigsaw untuk Meningkatkan Kemampuan Paedagogi Guru SDN Subah 01 Batang - Jaka, Jaka; Dwijayanti, Ida; Rasiman, Rasiman (CV. Supernova Office Stationary and Printing, 2022)
The problems in this study are (1) How to develop valid syllabus, lesson plans, materials and LKPD, (2) Can teachers' pedagogical competence be improved by In House Training Jigsaw Model? (3) Are there any differences in the tools developed by the teacher before participating in the In House Jigsaw Model Training and after? (4) What is the teacher's perception of the influence of the Jigsaw Model In House Training on the device development ability? The aims of this research are; (1) Developing the teacher's ability to develop valid learning tools, (2) Improving the pedagogical competence of teachers through In House Training Model Jigsaw, (3) Knowing the differences in tools developed by teachers before participating in In House Training Model Jigsaw and after, (4) The teacher has the correct perception of the development of learning tools after participating in the In House Training Model jigsaw. The population in this study were SD Subah 01 teachers consisting of 12 class teachers and subject teachers. The data collection method used is the questionnaire method. Data analysis used descriptive analysis, standardization test and hypothesis testing which included validity analysis to analyze the validity of the learning device product and t test to analyze the ability to construct learning tools before and after IHT. Data analysis using SPSS 1.6 application. From the results of the research it can be seen that the development of learning tools from the validation results of the three experts obtained an average of 70.33 with a Very Good predicate; -6.996, and sig (2-tailed) of 0.000. Based on the output table